Use of low dose misoprostol for induction of labour in a secondary hospital setting: a retrospective cohort study of a unique induction protocol - Cherian, Anne George; Reddy, Tamma Anusha; Dhinagar, Manoj Jacob; Arunraj, Deyya Anish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Induction of labour is a procedure often used in pregnant women where there are clear medical indications. There are various modalities of induction of labour which differ in outcomes and complications. Our aim was to look at how effective our protocol using misoprostol was in achieving delivery within 24 hours of the start of induction, the induction delivery interval, Caesarean section rates and its indications using Robsons classification, uterine hyperstimulation with FHR changes and oxytocin augmentation and its duration. Methods: This was a retrospective study which looked at the mode of induction and outcomes of women during the period from 1st February, 2021 to 31st July,2021. Results: There were 2574 deliveries in the period February 1st, 2021 to July 31st, 2021. We found more nulliparous women and obese women in the induced group. The main indication for induction was past dates and the mean induction to delivery interval among the women being induced was 32 hours (SD: 22.58). There were significantly higher women who experienced PPH and Caesarean sections were 2.100 (1.577- 2.793) times higher among women who were induced. Conclusions: Induction protocols need to be developed taking into consideration the advantages as well as complications associated with it and then tailor it according to infrastructure and personnel available.